'Publication favela' or bibliodiversity? Open access publishing viewed from a European perspective. (6th September 2018) - Mounier, Pierre
Abstract : A number of initiatives exist in European countries to support open scholarly communication in humanities and social sciences. This article looks at the work of Open Access in the European Research Area through Scholarly Communication (OPERAS), a consortium of 36 partners from all over Europe, including many university presses, that is working to build a future European infrastructure to address the challenges in open access publishing. Their initial study, OPERAS‐D, revealed a variety of models among the partners influenced by national cultures. Although the partners' activities were found to be fragmented, they also reflect the 'bibliodiversity' that exists in European societies. To address the challenge of fragmentation, it is argued that, by following a cooperative model, European actors can benefit by sharing expertise, resources, and costs of development for the good of all. As a future infrastructure to support open scholarly communication across Europe, OPERAS aims to coordinate a range of publishers and service providers to offer researchers and societies a fully functional web of services to cover the entire research lifecycle.